Amorphous Silicon / Crystalline Silicon Heterojunction Solar Cells - Fahrner, Wolfgang Rainer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Amorphous Silicon/Crystalline Silicon Solar Cells deals with some typical properties of heterojunction solar cells, such as their history, the properties and the challenges of the cells, some important measurement tools, some simulation programs and a brief survey of the state of the art, aiming to provide an initial framework in this field and serve as a ready reference for all those interested in the subject. This book helps to (3z(Bfill in the blanks(3y (Bon heterojunction solar cells. Readers will receive a comprehensive overview of the principles, structures, processing techniques and the current developmental states of the devices. Prof. Dr. Wolfgang R. Fahrner is a professor at the University of Hagen, Germany and Nanchang University, China.s
Introduction -- Useful material parameters -- Manufacturing -- Concepts -- Problems and challenges -- Measurement techniques -- Simulation -- Long term stability and degradation -- State of the Art -- Silicon based heterojunction solar cells in China.
Keywords: Engineering; Electric engineering; Optical materials; Materials Science; Optical and Electronic Materials; Nanotechnology and Microengineering; Energy Technology